Effects of predictability and controllability on task performance under time constraints. - Tan, Kenley Soon Chew. (2008)
Prior research has proposed two constructs, namely predictability and controllability, in mitigating the adverse effect of time pressure on task performance. In our studies, we investigate these two constructs separately and jointly on task performance under time pressure. Subjects’ performance is measured by the number of anagrams correctly solved under the given time constraints. In Study 1, we hypothesize that subjects when given predictability in the form of warning of time remaining will perform better than subjects without such warning. The results of Study 1 support the hypothesis. Our findings also reveal that subjects provided with warning in high time pressure condition perform just as well as subjects (without warning) in the low time pressure condition. Study 2 replicates Study 1 but with controllability as an additional variable. We posit that under time pressure, subjects provided with controllability over how they can complete a task will out perform subjects who are not provided with controllability. The results of Study 2 indicate that our hypothesis is only partially supported. Specifically, subjects provided with control performed better than subjects without control, only in the absence of time warning. Contrary to our expectation, the improvement in subjects’ task performance under time pressure given controllability is not greater when subjects are given time warning rather than no time warning. Instead, subjects provided with both controllability and time warning perform no better than subjects given only either control or warning.